Morbidity Profile of Stone Crusher Workers with Special Reference to Respiratory Morbidity - A Cross Sectional Study - Vinod Narkhede; Swarna Likhar; Mahesh K Mishra (Medsci Publications, 2012)
Background: The occupational environment at the stone crushing sites poses a potential health hazard to the workers. Exposure to heavy dust concentration from stone crushers, may produce several diseases. Methods: The present study was aimed to assess the morbidity profile of workers working in stone crusher industry. A cross-sectional study was carried out among the workers of the stone crushers located in Ratua at a distance of 23 km to the north of Bhopal city. The total workers working in the crusher are 287.Using interview technique as a tool for data collection demographic and occupational details of the subjects were recorded on the predesigned proforma which included questions regarding age, sex, educational status, socio-economic status, duration of employment and symptoms. The Peak Expiratory Flow Rate (PEFR) of the subject was measured using Peak flow meter/spirometer. Results: It was observed that in study population 62.72% were suffering from musculoskeletal problems followed by 31.36% subjects were having generalized weakness.29.96% subjects had breathing problem. Respiratory problems were higher among the subjects having duration of occupation more than 5 years than the subjects having duration of occupation less than 5 years (p<0.003). Conclusion: The present study concluded that the workers in the stone crushing industry are exposed to stone dust which leads to various morbidities especially musculoskeletal problems and respiratory problems. The respiratory problems are significantly associated with duration of exposure and decreased PEFR.